Review: Frontiers of materials science and engineering. (May 2014) - Ruan, G. L.; Velasco, J. I.; Vallés, C.; Li, Z. M.; Gloria, A.; Lin, W. Z.; Liu, F.
<x content-type="archive" xml:space="preserve">Abstract</x> Materials science and engineering is one of the hot research topics in the world, which is changing the way we live daily. As a result of this, the 2nd Global Conference on Materials Science and Engineering was held on November 20–22, 2013. During this event, more than 200 attendees discussed the frontiers of materials science and engineering. This editorial highlights some of these papers that present the new frontiers of materials science research in 2013.